The Application of Design Thinking in Understanding the Profile of Pancasila in the Elementary School Teacher Education Study Program - Robert Budi Laksana; Adrianus Dedy; Puji Ayu Rachmawati (Universitas Muhammadiyah Enrekang, 2024)
Abstract This study was motivated by knowing the application of design thinking in lectures in the PGSD study program. The benefit of this research is to know and become material for evaluating lecture activities carried out with the design thinking model. This research method is applied research. The data used is a combination of qualitative and quantitative data (mixed method). This research is the subject of research on 3rd semester students of the PGSD study program where these three courses are related to the formation of attitudes, knowledge and skills for elementary school teachers. As many as 80% of students who took the course had succeeded in making teaching media products independently and obtained topic ideas from ideas and arguments that had been latent, 100% of students stated that they were happy with the experience, this can be seen from each stage of the application of design thinking starting from the empathy, define, idea, prototype, implementation stages running well and fun. And succeeded in shaping the profile of Pancasila students with critical reasoning. Keywords: Design Thinking, PGSD Lectures, Pancasila Student Profile Abstrak Penelitian ini dilatarbelakangi mengetahui penerapan design thinking dalam perkuliahan di prodi PGSD. Manfaat penelitian ini adalah mengetahui dan menjadi bahan evaluasi kegiatan perkuliahan yang dilakasanakan dengan model design thinking. Metode penelitian ini adalah penelitian penerapan/applied research. Data yang digunakan adalah penggabungan data kualitatif dan dan kuantitatif (mixed method). Penelitian ini subyek penelitian pada mahasiswa semester 3 prodi PGSD dimana ketiga mata kuliah ini berhubungan dengan pembentukan sikap, pengetahuan dan keterampilan bagi guru SD. Sebesar 80% mahasiswa yang mengambil mata kuliah tersebut telah berhasil membuat produk media ajar secara mandiri dan memperoleh ide topik dari gagasan dan argument yang selama ini terpendam, sebesar 100% mahasiswa menyatakan senang dengan pengalaman, hal ini dapat dilihat dari setiap tahapan penerapan design thinking mulai dari tahap empaty, define, idea, prototype, implementasi berjalan dengan baik dan menyenangkan. Dan berhasil dalam membentuk profil pelajar Pancasila bernalar kritis. Kata Kunci: Design Thingking, Perkuliahan PGSD, Profil Pelajar Pancasila